Investigation of the impact of Ionospheric Scintillation on GNSS Performance over East Africa - Abiriga, Faustine; Amabayo, Emirant B; Jurua, Edward; Cilliers, Pierre J (Advances in Space Research, 2021)
In recent decades, the reliance on Global Navigation Satellite System (GNSS) applications is gaining ground in the East African region. This region lies within the low geomagnetic latitudes where signal scintillation events due to ionospheric irregularities are frequent. Signal scintillation events pose a considerable challenge to the carrier tracking loop of a Global Positioning System (GPS) receiver’s phase locked loop (PLL) and can result in cycle slips or even a total loss-of-lock. The cycle slips can degrade and disrupt satellitebased navigation systems, leading to significant positioning errors. In this study, data from the International GNSS Service (IGS) and SCIntillation Network and Decision Aid (SCINDA) for the year 2011 was used to statistically analyse the effects of ionospheric scintillation on satellite-based navigation over the East African region. Results obtained show that signal scintillation events follow a seasonal pattern with a higher percentage occurrence of amplitude scintillation events over phase scintillation events. Using the method of phase combinations, cycle slips were identified on GPS L-band signals. It was observed that the frequency of occurrence of cycle slips is higher on L2-frequency than on L1-frequency of the L-band. Furthermore, results showed that the presence of signal scintillation events in signal ray paths increased the errors in GPS receiver position measurement by up to about 10 m. This can compromise the reliability and accuracy of GPS applications in navigation. 2021 Published by Elsevier B.V. on behalf of COSPAR
Keywords: Ionospheric irregularities; Ionospheric scintillation; Global navigation satellite system; Loss-of-lock; GPS Position measurement error